Development of Digital Teaching Materials Based on Local Wisdom (Batu Lingga) in Improving Fifth Grade of Elementary School Cultural Literacy - SITI MALIHAH; Dase Erwin Juansah; yuyu yuhana (Jurnal Cakrawala Pendas, 2024)
Abstract This research is motivated by 1) Lack of use of interesting teaching materials in the science and science learning process; 2) There is no use of teaching materials that utilize local regional wisdom as an innovative and interesting learning resource at SDN Baros 3; 3) Lack of student interest in learning science and science; 4) The results of class V science and science learning at SDN Baros 3 are still not optimal. This research aims to describe and analyze the stages of development, feasibility, effectiveness, as well as describe and analyze students' responses to digital teaching materials based on local wisdom (Batu Lingga) in the science and sciences subject of cultural heritage material in class V UPT SDN Baros 3. This research uses ADDIE Research and Development model method which includes five stages including analysis, design, development, implementation, and evaluation. The results of this research show that 1) the feasibility test by material experts is included in the "very feasible" category with a score percentage of 96%, the feasibility test by media experts with a percentage of 80% is included in the "very feasible" category, the feasibility test by question experts with a percentage of 95% included in the "very feasible" category, and the feasibility test of the student response questionnaire obtained a percentage of 87% in the "very feasible" category; 2) effectiveness test through pretest and posttest with an N-Gain value of 0.82, which is included in the high category; 3) the results of students' responses to digital teaching materials based on local wisdom (Batu Lingga) are included in the very high category with a percentage of 92%. Thus, digital teaching materials based on local wisdom (Batu Lingga) for science and science subjects, cultural heritage material, are effective and suitable for use in the learning process. Keywords: development, digital teaching materials, local wisdom, cultural heritage, cultural literacy.